2020
DOI: 10.1186/s13287-020-01787-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced therapeutic effects of umbilical cord mesenchymal stem cells after prolonged treatment for HBV-related liver failure and liver cirrhosis

Abstract: Background: Umbilical cord mesenchymal stem cells (UCMSCs) have been demonstrated to have good therapeutic effects in the treatment of HBV-related liver diseases. However, the therapeutic effect of UCMSCs on HBV-related liver failure and liver cirrhosis and the variations in the efficacy of UCMSCs after different treatment courses remain poorly understood. Therefore, this study was designed to answer these two questions. Methods: This was an observational study that retrospectively considered a 3-year period d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Another distinct advantage is the decreased alloreactivity due to a low expression of class I and class II human leukocyte antigen [ 16 ]. Clinical studies have shown that UC-MSCs infusion significantly improved liver function in patients with decompensated liver cirrhosis [ 17 ] and increased the survival rates of patients with ACLF [ 8 , 13 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another distinct advantage is the decreased alloreactivity due to a low expression of class I and class II human leukocyte antigen [ 16 ]. Clinical studies have shown that UC-MSCs infusion significantly improved liver function in patients with decompensated liver cirrhosis [ 17 ] and increased the survival rates of patients with ACLF [ 8 , 13 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different reports highlighted as injection of UC-WJ-MSC in patients with chronic liver disorders or steatohepatitis ameliorate transaminase levels and lipid profile, reduces bilirubin and hyperglycemic profile, resulting in improved MELD score and overall survival (see ( Shahrbaf et al, 2022 ) for revision of such clinical studies). Beneficial clinical support offered by perinatal cells has been ascribed to repeated infusion rather than one single infusion ( Jia et al, 2020 ), in line with results offered by 3 decades of hepatocyte transplantation ( Gramignoli et al, 2015 ). Another source of perinatal MSC, amniotic membrane, has been described as instrumental to attenuate Kupffer autophagy and prevent Stellate activation ( Shahrbaf et al, 2022 ).…”
Section: Specific Sections Dedicated To Pnd Applicationsmentioning
confidence: 87%
“…Additionally, they can extend the overall survival rate in long-term follow-up [ 120 ]. Furthermore, endurance and extended donor cells have been ascribed to beneficial multiple infusion of UC-MSC rather than single injection [ 121 ]. In the context of other non-fibrotic chronic liver disorders, UC-MSC administration in models of non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) resulted in hyperglycemia decrement, reversal in transaminase escalation, improvement in lipid profile (such as triglyceride, low-density lipoprotein, or total cholesterol).…”
Section: Extraembryonic Msc In Support Of Liver Regeneration and Repairmentioning
confidence: 99%